Optimality Conditions for Weakly ϵ-Efficient Solutions of Vector Optimization Problems with Applications. (26th April 2019) - Capătă, Adela
Abstract: The aim of this article is to provide necessary and sufficient conditions for a feasible point to be a weakly ϵ -efficient solution of a vector optimization problem with cone constraints under generalized convexity notions and a weak constraint qualification. Our results permit to recover earlier established theorems.